(untitled) (Revista Apotheke, 2019)
This article focuses on the discussions of the naturalized pedagogical actions in visual arts developed in the Kindergarten institutions in Brazil. The examples, reflections and analyzes are derived from the author’s teaching experiences in the Pedagogy course at UFRGS and research developed at Porto Alegre Municipal Schools with teachers and children for 15 years. In addition to drawing an overview of art pedagogies in the context of early childhood education, we seek to understand and problematize the conceptions of child, art and education that guide such pedagogical practices in institutions that educate young children.